2019
DOI: 10.1002/mgg3.807
|View full text |Cite
|
Sign up to set email alerts
|

EIF4G1 is a novel candidate gene associated with severe asthenozoospermia

Abstract: Background Asthenozoospermia (AZS), also known as asthenospermia, is characterized by reduced motility of ejaculated spermatozoa and is detected in more than 40% of infertile patients. Because the proportion of progressive spermatozoa in severe AZS is <1%, severe AZS is an urgent challenge in reproductive medicine. Several genes have been reported to be relevant to severe asthenospermia. However, these gene mutations are found only in sporadic cases and can explain only a small fraction of severe AZS, so addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…QRT-PCR experiment of DNAH9-mRNA and immunofluorescence staining experiment of DNAH9-protein in sperm were performed in accordance with previous study [ 9 , 21 ]. The primary anti-DNAH9 was Anti-Dynein heavy chain antibody (ab133968, ABCAM).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…QRT-PCR experiment of DNAH9-mRNA and immunofluorescence staining experiment of DNAH9-protein in sperm were performed in accordance with previous study [ 9 , 21 ]. The primary anti-DNAH9 was Anti-Dynein heavy chain antibody (ab133968, ABCAM).…”
Section: Methodsmentioning
confidence: 97%
“…DNA from whole peripheral blood was used to perform WES and bioinformatic analysis. And the protocols were in accordance with previous research [ 9 , 21 ]. Sanger sequencing was performed to verify the identified variants and parental origins.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have presented that genetic disorders might be related to severe asthenospermia. Sha et al has found that EIF4G1 (OMIM: 600495) was a candidate gene of severe asthenospermia in one patient, whose sperm was revealed with mitochondrial sheath defects [9]. Similarly, Xu et al identi ed a homozygous SPAG17 (OMIM: 616554) mutation was associated with severe asthenozoospermia in a familial twins [10].…”
Section: Introductionmentioning
confidence: 99%